Oocytes : Maternal Information and Functions - Kloc, Malgorzata (Springer, 2017)
This book combines the most recent knowledge on the maternal, i.e. oocyte/egg-specific, molecules and processes. The volume covers the most recent advances in a plethora of subjects such as: maternal transfer of immunity, localized RNAs functions and mechanisms of RNA localization, transcriptional repression of maternal messages, maternal inheritance and maternal role of CRISPR/Cas9-based genome editing, chromatin remodeling and epigenetic modifications, maternal function of nucleosomes, maternal mitochondria and energy supply, role of bacterial symbionts and their maternal transmission, acquisition of oocyte polarity and evolution of maternal effect genes, germ plasm and oosome origin and functions, mechanisms of oocyte activation and soma germ cells communication. Currently, no other book on the market combines such a comprehensive list of subjects in one volume. Moreover, the information provided is a cross-section through oocytes from various invertebrate a nd vertebrate species, which is another unique feature of this book. The readers, therefore, get a completely new and invaluable perspective on all covered subjects.
Keywords: Ovum.; elektronické knihy; electronic books